Factor that Influence on PHBS Students Female of Islamic Boarding School Al – Huda Kediri City Based on Health Belief Model Theory - Ridha Rachmathiany; Byba Melda Suhita; Nurdina Nurdina (Journal for Quality in Public Health, 2020)
Boarding school in Indonesia still a lot of problem that are so classic that is about the health of students and problem with diseases. Boarding school must cooperate with health authorities to coaching health for the students, so that the pattern of living behavior is clean and healthy for the students and communities in the boarding schools and their environmental communities. The purpose of the research is exploration factors that influence on PHBS student female Boarding School Al-Huda Kediri City based on the theory of Health Belief Model. The design of research used qualitative research with a case study approach. Data collection uses in-depth interview techniques (in depth interview) with semi -structured questions with samples of 16 informant. From result research shows the science of PHBS is ignorance. PHBS student female is an indicator PHBS boarding school has not been fulfilled. PHBS are important to implement at boarding school. While information about PHBS is require in boarding school. Attitude of PHBS student female is implementing a picket schedule. Obstacles doing PHBS is the individual's own attitude. Management of boarding school gives attention to PHBS. Management of boarding school gives information about PHBS. Management of boarding school help students about PHBS at boarding school. Importance of support from boarding schools. There are motivation yourself to increase PHBS. Importance of the motivation from friends /management boarding school to increase PHBS. Based on the research it needs to be done further research on environmental health in boarding schools.